A Római Egyetemi Magyar Tanszék 85 éve - Sárközy, Péter (Gerundium, 2017)
The History of the Hungarian Chair at the University of Rome. The first Chair of Hungarian Literature and Language in Italy was established at the University of Rome La Sapienza in 1930. At first, the chairmen of the position were the professional directors of the Hungarian Academy in Rome. Between the two world wars Hungarian was also taught in Bologna, Firenze, Milano, Napoli and Padova. Since 1965 in Padova and in Rome Hungarian visiting professors were teaching: in Rome János Balázs, József Szauder and Tibor Klaniczay academics, afterwards Péter Sárközy from 1979 to 2015. At the University of Rome has been founded in 1985 the Interuniversity Centre for Hungarian Studies, which publishes the „Rivista di Studi Ungheresi” (Hungarian Studies Review).Hungarian Literature and Language are taught nowadays in Italy at universities of Bologna, Firenze, Napoli, Padova, Roma and Udine.